Exploring the Drivers and Nature of Corporate Social Responsibility Practice from an African Perspective - Hamidu, Aminu Ahmadu; Haron, Md. Harashid; Amran, Azlan (International Review of Management and Marketing, 2016)
This paper explored the major drivers of CSR practice in Africa. In the process of explaining the nature of CSR it explained the evolutionary trend of CSR through the whole century and also touched on the CSR orientations and a recognised framework for determining the orientations through the four responsibilities or dimensions. The CSR orientations explained the priority accorded to some sets of activities representing the CSR practice of organisations in Africa from different literatures. The paper found out that CSR practice in Africa is determined by philanthropic responsibilities derived from cultural and religious practice in Africa. The practice of CSR as a strategy for achieving profitability, competitiveness, standard compliance, ethical and legal considerations, stakeholder management and engagement and achievement of sustainable development is less emphasised in the African context when compared to the western perspective of CSR practice Keywords: Corporate Social Responsibility, CSR practice in Africa, CSR drivers, CSR orientations, CSR pyramid, JEL Classification: M14